1970
DOI: 10.1254/jjp.20.187
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Collateral Vasodilator Action of N-Ethoxycarbonyl-3-Morpholinosydnonimine (Sin-10) in Heart With Chronic Coronary Insufficiency in Dogs

Abstract: Effects of the sydnonimine derivatives on cardiovascular system have been studied(1-5), and the results in our laboratory are summarized as follows : 1) the substitution by the group containing nitrogen with -N-N linkage in the 3-position (SIN-series) showed vasodilator and consequently hypotensive effects resembling to those of nitrites, and 2) N-acylation of imino group of sydnonimine made the compounds stable chemically (6), which probably resulted in gradual development and prolongation of the hypotensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
2
5
0
2
Order By: Relevance
“…These results need to be considered with regard to the experimental setup, taking into account the relevance of standard electrocardiographic changes as an index of pathophysiological precursors of lifethreatening ventricular arrhythmias (Kaplinsky et al, 1979;Menken et al, 1979;David et al, 1982;Jouve et al, 1986a) and the reported effects of molsidomine in improving directly or indirectly the oxygen supply in ischaemic areas ofthe left ventricle (Hirata & Kikuchi, 1970;Berdeaux et al, 1978;Fiedler, 1982;Fiedler et al, 1982;Nitz & Martorana, 1985 vU Holzman, 1985). In contrast, the antiplatelet effects of the drug do not seem to contribute importantly to these effects of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results need to be considered with regard to the experimental setup, taking into account the relevance of standard electrocardiographic changes as an index of pathophysiological precursors of lifethreatening ventricular arrhythmias (Kaplinsky et al, 1979;Menken et al, 1979;David et al, 1982;Jouve et al, 1986a) and the reported effects of molsidomine in improving directly or indirectly the oxygen supply in ischaemic areas ofthe left ventricle (Hirata & Kikuchi, 1970;Berdeaux et al, 1978;Fiedler, 1982;Fiedler et al, 1982;Nitz & Martorana, 1985 vU Holzman, 1985). In contrast, the antiplatelet effects of the drug do not seem to contribute importantly to these effects of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Other potentially useful pharmacological properties of molsidomine have been described in the dog. These include: a coronary collateral vasodilator action in hearts with coronary insufficiency (Hirata & Kikuchi, 1970), improved endocardial blood flow (Berdeaux et al, 1978), a reduction of both occlusive coronary artery thrombosis and myocardial ischaemia (Fiedler, 1982), decreased infarct size after coronary artery ligation , and an anti-ischaemic effect following controlled reduction of coronary perfusion as assessed by ST segment changes in multiple unipolar epicardial leads (Nitz & Martorana, 1985). Finally, a reduction in the incidence of post-reperfusion ventricular fibrillation in a non-controlled study was observed after left anterior descending coronary artery ligation in 8 dogs (Nitz & Martorana, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The fall in coronary flow after molsidomine was not accompanied by changes in coronary sinus blood oxygen content so that the flow reduction most likely reflects the consequences of reduced myocardial oxygen demand. These data, however, are not necessarily conflicting as the dogs in the earlier study (8) were chronically ischemic with ample time to develop functional coronary collateral vessels, whereas the acute, short-lasting coronary artery occlusion in the latter study (5) did not allow the hearts enough time to open collaterals for sufficient blood supply to the ischemic endocardial muscle. Hence, the intravenous administration of molsidomine does not directly affect the heart and coronary circulation.…”
Section: Discussionmentioning
confidence: 80%
“…The latter was recently shown for molsidomine as the result of longlasting venodilation (6,9) accompanied by a reduction in preload with little effects on afterload (1, 3,10). However, conflicting results exist with respect to molsidomine's effects upon coronary collateral vessels: whereas some investigators reported dilation of collateral vessels in canine hearts (1, 8,15), others could not establish changes in coronary collateral blood flow after molsidomine (5). As a contribution to these aspects of the mechanism of anti-anginal molsidomine actions, we have investigated the effects of the drug on the dog heart's non-constricted left coronary artery blood flow in acute experiments.…”
Section: Introductionmentioning
confidence: 96%
“…This is very favourable with respect to the possible application of the drug in coronary heart disease for the following reasons: 1. This does not exclude an increase and a beneficial redistribution of myocardial blood flow supplied via collaterals (10). A concomitant, significant reduction in peripheral resistance is not desirable (24).…”
Section: Discussionmentioning
confidence: 99%